Pemidanaan terhadap Perbedaan Pemahaman: Analisis Hak Asasi Manusia atas Perkara Penodaan Agama di Indonesia - Moch. Choirul Rizal; Michelle Salma Khotom Aji; Muhamad Atji Firmansyah; Unsa Elen Purwanti (Badan Strategi Kebijakan Hukum, 2025)
The right to have different interpretations of mainstream religious teachings in Indonesia can lead to criminal penalties. In practice, judges often rely on expert testimony to gain confidence that